Physics calculator application with matlab as a learning media to thermodynamics concept - Kintan Utari; Neng Nenden Mulyaningsih; Irnin Agustina Dwi Astuti; Yoga Budi Bhakti; Zulherman Zulherman (Momentum: Physics Education Journal, 2021)
In the material of thermodynamics, many physics equations make students abstract in understanding the material. It is necessary to have a learning media to be able to visualize the thermodynamics material. Matlab is usually used in numerical analysis. Currently, Matlab can be used as a medium for learning physics by students to understand the material well. This study aims to develop a physics calculator application on the subject of thermodynamics using Matlab software. The research method used in this research is the research development method with the development model of ADDIE (Analysis, Design, Development, Implementation and Evaluation). The instruments used in this study were a validation test questionnaire and a student response questionnaire. The analysis technique applied is the descriptive analysis and the average analysis techniques. The results developed in this study are in the form of a Physics calculator application that helps physics calculations on thermodynamic material. The average validation result by material experts and media experts is 83.1%, with the "Good" category. In other words, according to experts, this media is suitable for use in physics learning. This application also received a positive response from students, with an average student response score of 79.8%. This application is also equipped with materials, physics calculators, physics simulations and question exercises so that it is expected to help students understand physics learning in thermodynamics material.